Prediction of osteoporotic fractures by postural instability and bone density. Issue 6912 (30th October 1993) - Nguyen, T; Sambrook, P; Kelly, P; Jones, G; Lord, S; Freund, J; Eisman, J
Abstract : OBJECTIVE–To investigate the utility of risk factors such as bone mineral density, lifestyle, and postural stability in the prediction of osteoporotic fractures. DESIGN–Longitudinal, epidemiological, and population based survey. SETTING–City of Dubbo, New South Wales. SUBJECTS–All residents of Dubbo aged > or = 60 on 1 January 1989. MAIN OUTCOME MEASURE–Incidence of fracture for individual subjects. RESULTS–The overall incidence of atraumatic fractures in men and women was 1.9% and 3.1% per annum respectively. The predominant sites of fracture were hip (18.9%), distal radius (18.5%), ribs and humerus (11.9% in each case), and ankle and foot (9.1% and 6.6% respectively). Major predictors of fractures in men and women were femoral neck bone mineral density, body sway, and quadriceps strength. Age, years since menopause, height, weight, and lifestyle factors were also correlated with bone mineral density and body sway and hence were indirect risk factors for fracture. Discriminant function analysis correctly identified 96% and 93% (sensitivities 88% and 81%) of men and women, respectively, who subsequently developed atraumatic fractures. Predictions based on this model indicated that a woman with a bone mineral density in the lowest quartile in the hip together with high body sway had a 8.4% probability of fracture per annum. This represented an almost 14-fold increase in risk of fracture compared with a woman in the highest bone mineral density quartile with low postural sway. An individual with all three predictors in the "highest risk" quartile had a 13.1% risk of fracture per annum. CONCLUSIONS–Bone mineral density, body sway, and muscle strength are independent and powerful synergistic predictors of fracture incidence.